PREVALENCE AND CHEMOTHERAPY OF COCCIDIOSIS IN DOGS IN AND AROUND LAHORE- PAKISTAN - A. Younas; M. S. Khan; M. Ijaz; a K. Ashraf; M. M. Ali; I. Khan; b A. Rehman (Journal of Animal and Plant Sciences, 2014)
The present study was undertaken to ascertain the prevalence and chemotherapy of coccidiosis in dogs. For this purpose a total of 300 fecal samples were collected from different dogs in and around district Lahore. All the study animals were divided into three age groups. Collected samples were processed and examined with the help of light microscope for the presence of protozoan oocytes. In present study, overall16.33% prevalence of coccidiosis was recorded. The chi-square analysis revealed significantly (p<0.001) higher prevalence of coccidiosis in young dogs. The prevalence of coccidiosis in different age groups such as  <6 months,  up to 6-12 months and  1-2 year age was 75.51, 6.08 and 3.67% respectively. The frequency analysis (OR=1.41[reciprocal =0.71]) showed non-significant difference in both male and female dogs. However it was non-significantly higher in male (18.67%) as compared to female (14%). The efficacy of sulfadimethoxine and Furazolidone was 98.29 and 96.64% respectively, after 14th dayof treatment, showing the useful effects of both drugs in dogs.
Keywords: prevalence; coccidiosis; sulfadimethoxine; furazolidone; dogs